2012
DOI: 10.2174/1874091x01206010116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carotenoid-protein Complexes and Gene Expression Analysis Associated with Carotenoid Sequestration in Pigmented Cassava (Manihot Esculenta Crantz) Storage Root

Abstract: Carotenoid-protein complex (CPC) was isolated from chromoplast-enriched suspensions of cassava storage root (CSR) using size exclusion chromatography and characterized. Peptide sequences (LC_MS/MS spectrum) obtained from CPC and their corresponding proteins were obtained using publically available databases. Small Heat Shock Proteins (sHSPs) were the most abundant proteins identified in the CPC. Western blot analysis showed that Fribrillin and Or-protein were present in chromoplast-enriched suspensions of yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…It was reported that the HSPs were involved in response to environmental stress such as heat, cold, drought and salinity stress [56, 57]. In plants, the HSPs have been speculated to act as an antioxidant under oxidative stress [58] or as an important tool for genetic manipulation of protein content in cassava storage root contributing to a natural sink for protein and carotenoid accumulation in intense yellow roots [59]. Further elucidation of the roles of HSPs in binding specifically with PPD would provide our understanding of the molecular machinery controlling PPD onset.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the HSPs were involved in response to environmental stress such as heat, cold, drought and salinity stress [56, 57]. In plants, the HSPs have been speculated to act as an antioxidant under oxidative stress [58] or as an important tool for genetic manipulation of protein content in cassava storage root contributing to a natural sink for protein and carotenoid accumulation in intense yellow roots [59]. Further elucidation of the roles of HSPs in binding specifically with PPD would provide our understanding of the molecular machinery controlling PPD onset.…”
Section: Discussionmentioning
confidence: 99%
“…The 26.4 KDa heat-shock protein (A5A8U9), which was present in the line with the addition of 7 H ch could also be playing a key role in the accumulation of carotenoids as small heat shock proteins were found to be the most abundant proteins present in the carotenoid-protein complexes of cassava roots, suggesting their involvement in the accumulation of these pigments. [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…source of starch, but not of protein and vitamins (CARVALHO et al, 2012). However, the pink root has the genetic potential to become a source of lycopene for human consumption (CARVALHO et al, 2016).…”
Section: Crop Productionmentioning
confidence: 99%
“…(Table 4), with the 2010/2011 crop season highlighting clone 406/08 (39.19 μg g -1 dry mass) and the 2011 / 2012 crop season the clone 341/08 (42.80 μg g -1 of dry mass) (Table 4). The higher absolute values of total carotenoids in clones with pink root color compared to cream and yellow are probably due to the fact that they accumulate lycopene and β-carotene in their reserve roots (CARVALHO et al, 2012;SILVA et al, 2014). Regarding the hydrocyanic acid (HCN) content in the cassava stock roots, all clones presented amounts below 100 mg kg -1 (Table 3); and are therefore, suitable for to being commercialized fresh.…”
Section: Fv Gl ---------------------------------------------------Qm-mentioning
confidence: 99%